ANALISIS LOYALITAS PELANGGAN TOKO KOPI TUKU DKI JAKARTA: PERAN KUALITAS PELAYANAN, ATMOSFER TOKO, KEPUASAN PELANGGAN - Jericho Geovanni Salim; Galuh Mira Sakti (MANAJEMEN DEWANTARA, 2026)
The goal of this resarch to investigate the affect of service quality and store atmosphere on customer loyalty, with customer satisfaction acting as a mediator, specifically at Tuku Coffee Shop in DKI Jakarta. Adopting a quantitative methodology with a descriptive design, the research employed non-probability sampling through purposive techniques. Data collection involved distributing online questionnaires to 248 participants residing in DKI Jakarta who had patronized Tuku Coffee Shop at least twice. Analysis was performed using SmartPLS 4.0 with PLS SEM. The results demonstrate that service quality and store atmosphere exert a positive and significant impact on both customer satisfaction and loyalty. Additionally, customer satisfaction shows a positive and significant effect on loyalty. Mediation analysis further confirms that service quality and store atmosphere serve as mediators in the link between customer satisfaction and loyalty.